Relationship between motor abilities and severity of autism spectrum disorder - Cvijetić Marija; Gagić Sanja (Specijalna Edukacija i Rehabilitacija, 2017)
According to the findings in literature, motor skills of children with autism spectrum disorders generally differ from age expectations and are increasingly being associated with speech and language and social development, and adaptive behavior. The aim of the research was to determine the relationship between the development level of fine and gross motor skills and autism severity of children with autism spectrum disorder. The sample included 30 children with autism spectrum disorder and associated intellectual disability, seven to 19 years of age (M=11.97; SD=3.70). The assessment was conducted using the Peabody Motor Development Scale, the Vineland Adaptive Behavior Scale, and the criteria for describing the level of severity of autism spectrum disorder (APA, 2013). The results have shown that participants' motor skills significantly correlate with social communication (Peabody fine motor skills r=-0.452; p=0.012; Vineland fine motor skills r=-0.511; p=0.004; Vineland total r=-0.391; p=0.032) and restricted, repetitive behaviors (Peabody fine motor skills r=-0.383; p=0.037; Vineland fine motor skills r=-0.433; p=0.017; Vineland total r=-0.371; p=0.044). Lower level of autistic symptomatology is associated with higher motor achievements. It is necessary to pay more attention to the assessment and treatment of motor skills in children with autism spectrum disorder, given the established delay in the development of these skills, and bearing in mind their relationship with the severity of the symptoms of autism spectrum disorder. Timely identification of motor disorders would allow the use of early treatment and potentially lead to better results, compared to later inclusion in intervention programs.